Implementasi Model Pembelajaran Problem Based Learning (PBL) Dengan Media Berburu Ubur-Ubur Terhadap Kemampuan Berpikir Kritis - Suci Restiana Devi; Kurniawan Kurniawan; Edi Fitriana Afriza (Pusat Riset dan Inovasi Nasional, 2026)
The problem in this study is the low critical thinking ability of students. The goal is to improve students' critical thinking skills in economics by implementing the Problem Based Learning (PBL) learning model assisted by jellyfish hunting media on students' critical thinking skills in economics subjects in grade XI of SMAN 1 CIAMIS. The method used was quasi-experimental with a nonequivalent control group design research. The population in this study is classes XI-5 to XI-12. The research sample used was class XI-8 as an experimental class and XI-9 as a control class with a non-probability sampling technique in the form of purposive sampling. Based on the results of the study, it was explained that there was a significant difference in the improvement of students' critical thinking skills by using the Problem Based Learning (PBL) learning model assisted by jellyfish hunting media, where the average postest score was superior compared to the average postest using the conventional learning model in the control class, thus it can be concluded that the Problem Based Learning learning model (PBL) with the help of jellyfish hunting media has an effect on students' critical thinking skills.